A Central Coordination System for managing a large supply base through supply chain collaboration. (6th May 2010) - Chung, S.H.; Lau, H.C.W.; Chan, F.T.S.
Competitive edge from the advanced technology is being replaced. Organisations are now situating in a rapidly dynamic world full of suppliers, whom can probably produce similar products or even better products as time goes. To secure the competitive advantages, purchasing managers have to continuously searching for new suppliers, monitoring and evaluating them. However, this may not be a realistic task because it can dramatically increase the management costs and administration time of an individual organisation. Driven by these reasons, this article proposes a new supplier management approach – a Central Coordination System (CCS). CCS implements the idea of supply chain collaboration. Through the collaboration of information sharing, this article suggests the establishment of a supplier's information database, which helps customers to manage their suppliers more efficiently, economically and reliably.